Antimicrobial activity of Turkish Viurnum species (Bangladesh Journal of Botany, 2014)
Antimicrobial activities of aqueous and ethanolic extracts of Viburnum opulus L., V. orientale Pallas, V. tinus L. and V. lantana L. against Staphylococcus aureus ATCC 25923, S. aureus ATCC 43300 (MRSA), Bacillus subtilis ATCC 6633, Escherichia coli ATCC 25922, Pseudomonas aeruginosa ATCC 27853, Klebsiella pneumoniae RSKK 574 and Candida albicans ATCC 10231 were carried out. The disc diffusion and tube dilution techniques were used to determine the antimicrobial activities of plant extracts. The ethanolic extracts of tested species of Viburnum exhibited better antimicrobial activity than that of aqueous extracts. DOI: http://dx.doi.org/10.3329/bjb.v42i2.18044 Bangladesh J. Bot. 42(2): 355-360, 2013 (December)